الأعمال الطبية الحديثة بين الأحكام الفقهية والقانون الإندونيسي (دراسة مقاصدية في طفل الأنابيب و منع الحمل و زراعة الأعضاء) - Fajar, Ricky (Universitas Muhammadiyah Surakarta, 2016)
A The purpose of this study is to describe the surgery of modern medicine in in vitro fertilisation (IVF), contraception and organ transplants between Indonesian regulation, it’s seen from the viewpoint of